Recurrent Stress-Induced Cardiomyopathy: A Case Report and Review Article - Suman krishna Kotla; Cyril Nathaniel (Case Reports in Medicine)
ABS is a unique acute cardiac syndrome and a recently recognized form of transient left ventricular dysfunction. It mimics ACS in clinical presentation (chest pain and dyspnea) and specific ECHO findings in the absence of significant coronary lesions. This rare entity accounts for 2.2% of ST segment elevation ACS. Pathophysiology mostly correlates to stress-induced catecholamine release. The syndrome is predominant in females, mostly in the postmenopausal age group. It should be initially managed according to the guidelines of ACS. The prognosis for apical ballooning syndrome is generally favorable with inpatient hospital mortality less than 2%. Reports of a single episode of ABS are common in recent medical literature; we report a rare case of recurrence that provides more insight into the nature of this unique syndrome.